Genetic Control and High Temperature Effects on Starch Biosynthesis and Grain Quality in Rice - Zhang, Hua; Xu, Heng; Jiang, Yingying; Zhang, Heng; Wang, Shiyu; Wang, Fulin; Zhu, Ying (Frontiers in Plant Science, 2021)
Grain quality is one of the key targets to be improved for rice breeders and covers cooking, eating, nutritional, appearance, milling and sensory properties. Cooking and eating quality are mostly of concern to consumers and mainly determined by starch structure and composition. Although many starch synthesis enzymes have been identified and starch synthesis system has been established for a long time, novel functions of some starch synthesis genes have continually been found, and many important regulatory factors for seed development and grain quality control have recently been identified. Here, we summarize the progress in this field as comprehensively as possible and hopefully reveal some underlying molecular mechanisms controlling eating quality in rice. The regulatory network of amylose content (AC) determination is emphasized, as AC is the most important index for rice eating quality (REQ). Moreover, the regulatory mechanism of REQ, especially AC influenced by high temperature which is concerned as a most harmful environmental factorduring grain filling is highlighted in this review.